2008
DOI: 10.1152/ajprenal.00306.2007
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of low-dose carbon monoxide against renal fibrosis induced by unilateral ureteral obstruction

Abstract: Tubulointerstitial fibrosis is a hallmark of chronic progressive kidney disease leading to end-stage renal failure. An endogenous product of heme oxygenase activity, carbon monoxide (CO), has been shown to exert cytoprotection against tissue injury. Here, we explored the effects of exogenous administration of low-dose CO in an in vivo model of renal fibrosis induced by unilateral ureteral obstruction (UUO) and examined whether CO can protect against kidney injury. UUO in mice leads to increased extracellular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 60 publications
3
35
0
Order By: Relevance
“…We have previously reported that exposure to low-dose CO (250 ppm) markedly reduced collagen deposition in the kidneys after UUO in mice (34). Moreover, low-dose CO treatment inhibited the induction of ␣-smooth muscle actin and major ECM proteins, Col-I and fibronectin, in the mouse kidneys after UUO.…”
Section: Carbon Monoxide (Co)-induced Autophagy Stimulates Degradatiomentioning
confidence: 86%
See 4 more Smart Citations
“…We have previously reported that exposure to low-dose CO (250 ppm) markedly reduced collagen deposition in the kidneys after UUO in mice (34). Moreover, low-dose CO treatment inhibited the induction of ␣-smooth muscle actin and major ECM proteins, Col-I and fibronectin, in the mouse kidneys after UUO.…”
Section: Carbon Monoxide (Co)-induced Autophagy Stimulates Degradatiomentioning
confidence: 86%
“…CO is an endogenous product of heme oxygenase activity that has been shown to exert potent cytoprotection against tissue injury including kidney fibrosis (34), and recently CO has been shown to induce autophagy (48). Lowdose CO (250 ppm) increased the expression and activation of the autophagic protein LC3 in the mouse lung, and in cultured human alveolar (A549) or bronchial epithelial cells in a timedependent manner (48).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations